FAKTOR-FAKTOR YANG MEMPENGARUHI PENCEGAHAN INFEKSI NOSOKOMIAL DI RUANG ICU DAN RAWAT INAP LANTAI 3 RSU SARI MUTIARA MEDAN - Agnes Silvina Marbun (Jurnal Online Keperawatan Indonesia, 2018)
Nosocomial infection is an infection found in hospitals, which are caused by microorganisms such as bacteria, viruses, fungi and parasites. Factor is the lack of nursing knowledge, attitudes or behavior that is not good, facility maintenance, and supervision of nurses can also become one of the medium of transmission of nosocomial infections. The purpose of this study was to determine the factors that influence the incidence of nosocomial infections in the Intensive Care Unit (ICU) and the 3rd floor inpatient unit Sari Mutiara Hospital Medan. This research is a descriptive cross sectional pendenkatan. Where populations are all nurses in the ICU and inpatient unit on the 3rd floor which amounted to 30 people as well as sample. The results showed that factors associated dengen incidence of nosocomial infections is not knowledge that is 56.7% majority, the majority is not a good attitude as much as 76.7%, fasitas not good nursing supervision 53.3% and 53.3% which is not good. The results using the Spearman rank statistical test showed that the incidence of infection associated with the knowledge noskomial with p = 0.003, p = 0.21 attitudes, facilities with p = 0.030 and p = 0.002 supervision. Suggested to the hospital to be able to improve education and training for nurses.